Book Review: The Good Shepherd: A Thousand – Year Journey from Psalm 23 to the New Testament - Sinaga, Andri Vincent (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This book review examines Kenneth E. Bailey's “The Good Shepherd: A Thousand-Year Journey from Psalm 23 to the New Testament.” Bailey, a leading Biblical scholar with nearly five decades of experience in the Middle East, traces the development of the “Good Shepherd” theme from Psalm 23 to the New Testament. With a strong intertextual approach, Bailey shows the continuity of this theme through the writings of the prophets to the gospels and epistles of the New Testament. The book is divided into nine chapters, each focusing on a specific part of the Bible. Beginning with an in-depth analysis of Psalm 23, Bailey explores the dual role of the shepherd in ancient Middle Eastern culture. He then develops this theme through the prophets, portraying God as the shepherd who restores His people. In an analysis of the Gospels, Bailey shows how Jesus identifies Himself as the Good Shepherd, contrasting Him with failed leaders. The book concludes with a discussion of the Letter of 1 Peter, which emphasizes the importance of humble leadership in the church. Bailey uses a variety of methodological approaches, including in-depth literary and rhetorical analysis, Middle Eastern social and cultural contextualization, and intertextual approaches. The book's main strength lies in its use of in-depth Middle Eastern cultural context and strong rhetorical analysis, helping readers understand the development and relevance of the metaphor of the “Good Shepherd”.